If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 + -9(d + -5) = -2 Reorder the terms: 16 + -9(-5 + d) = -2 16 + (-5 * -9 + d * -9) = -2 16 + (45 + -9d) = -2 Combine like terms: 16 + 45 = 61 61 + -9d = -2 Solving 61 + -9d = -2 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-61' to each side of the equation. 61 + -61 + -9d = -2 + -61 Combine like terms: 61 + -61 = 0 0 + -9d = -2 + -61 -9d = -2 + -61 Combine like terms: -2 + -61 = -63 -9d = -63 Divide each side by '-9'. d = 7 Simplifying d = 7
| -148=4(6+7x)-4 | | c+5=41 | | 24=2x+3(2x) | | 5.8=-8+x | | 6(x+4)-5=1 | | 3+5w=9+4w | | -2x+2=-2x+1 | | 7=n/7+9 | | 2n^2-3n+4=0 | | (9x^2)-131x+450=0 | | -3(y-6)=30 | | 2y+x=-9 | | Y+11=-11 | | 5-x-1=x-2 | | Y+11=11 | | 11=3n-10 | | -29x+2=-2x+1 | | -7(b+3)=7 | | (x+18)(x-6)=25 | | 3b-1(6-b)=22 | | x+3x=50000 | | 2r=72 | | 2(x+4)=4+4x | | Z^2-2z-24=0 | | 38(24-3.5x)=16(3x-10)+76.5 | | u^2+u-52=0 | | 3(x+2)=-2(x+4) | | -4(e+6)=-12 | | 4x+3=1x | | .65l+70=l | | 12x-5=24x+3 | | -4.65+0.19x=14.92 |